Effects of carbohydrate and protein supplement strategies on endurance capacity and muscle damage of endurance runners: A double blind, controlled crossover trial. Issue 1 (31st December 2022) - Liang, Yiheng; Chen, Yan; Yang, Fan; Jensen, Jørgen; Gao, Ruirui; Yi, Longyan; Qiu, Junqiang
ABSTRACT: Background: The purpose of this study is to explore the effect of carbohydrate only or carbohydrate plus protein supplementation on endurance capacity and muscle damage. Methods: Ten recreationally active male runners (VO2max : 53.61 ± 3.86 ml/kg·min) completed run-to-exhaustion test three times with different intakes of intervention drinks. There was a 7-day wash-out period between tests. Each test started with 60 minutes of running at 70% VO2max (phase 1), followed by an endurance capacity test: time-to-exhaustion running at 80% VO2max (phase 2). Participants randomly ingested either 1) 0.4 g/kg BM carbohydrate before phase 1 and before phase 2 (CHO+CHO), 2) 0.4 g/kg BM protein before phase 1 and 0.4 g/kg BM carbohydrate before phase 2 (PRO+CHO), or 3) 0.4 g/kg BM carbohydrate before phase 1 and 0.4 g/kg BM protein before phase 2 (CHO+PRO). All subjects ingested carbohydrate (CHO) 1.2 g/kg BM during phase 1, and blood samples were obtained before, immediately, and 24 h after exercise for measurements of alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatine kinase (CK), and myoglobin (MB). Results: There was no significant difference in time to exhaustion between the three supplement strategies (CHO+CHO: 432 ± 225 s; PRO+CHO: 463 ± 227 s; CHO+PRO: 461 ± 248 s). However, ALT and AST were significantly lower in PRO+CHO than in CHO+CHO 24 h after exercise (ALT: 16.80 ± 6.31 vs. 24.39 ± 2.54 U/L; AST: 24.06 ± 4.77 vs. 31.51 ± 7.53 U/L, p < 0.05). MB was significantly lower in PRO+CHO and CHO+PRO than in CHO+CHO 24 h after exercise (40.7 ± 15.2; 38.1 ± 14.3; 64.3 ± 28.9 ng/mL, respectively, p < 0.05). CK increased less in PRO+CHO compared to CHO+CHO 24 h after exercise (404.22 ± 75.31 VS. 642.33 ± 68.57 U/L, p < 0.05). Conclusion: Carbohydrate and protein supplement strategies can reduce muscle damage caused by endurance exercise, but they do not improve endurance exercise capacity.